2016
DOI: 10.1007/s10792-016-0423-0
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated versus conventional corneal collagen cross-linking in patients with keratoconus: an intrapatient comparative study

Abstract: Accelerated CXL with 9 mW/cm irradiation for 10 min had similar refractive, visual, keratometric, and aberrometric results and less adverse effects on the corneal thickness and endothelial cells as compared with the conventional method after 12 months follow-up. However, randomized clinical trials with longer follow-ups and larger sample sizes are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 33 publications
3
52
0
1
Order By: Relevance
“…Sadoughi et al. () showed no significant correlation between changes in ECD and CCT in any of the groups. Thus, it is supposed that in practice, endothelial cell loss does not depend on whether the cornea is rather thin or thick.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Sadoughi et al. () showed no significant correlation between changes in ECD and CCT in any of the groups. Thus, it is supposed that in practice, endothelial cell loss does not depend on whether the cornea is rather thin or thick.…”
Section: Discussionmentioning
confidence: 91%
“…; Sadoughi et al. ) postoperatively. Although C‐CXL showed a smaller reduction in CH and CRF, statistical significance was missed comparing changes among both groups (p = 0.21 and 0.46 respectively) (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Table 3 is a summary of previous studies on the longterm changes in the central ECD (spanning more than 2 years), and those on the changes in the central CV and HEX after CXL. Several studies on corneal endothelial cell after CXL have been published, however all studies focused on the endothelial cell density and the morphology only in the central cornea in post-CXL eyes [10][11][12][13][14][15][16][17][18][19][20][21]. The mean central ECD loss was − 0.1 to 7.5%, which was largely different among previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies on corneal endothelial cell after CXL have been published, however all studies focused on the endothelial cell density and the morphology only in the central cornea in post-CXL eyes. [10][11][12][13][14][15][16][17][18][19][20][21] The mean central ECD loss was -0.1% to 7.5%, which was largely different among previous studies. We speculate that it is still challenging to exactly determine the ECD in some eyes with progressive keratoconus, as a result of the presence of apical scarring and/or a steep curvature of the cornea.…”
Section: Discussionmentioning
confidence: 99%
“…22 In this study, we found no significant changes in the peripheral CV or HEX after CXL, which was the same as previous studies with no significant changes in the central CV or HEX. 13,15,[17][18][19]21 The cellular stress levels of the cornea are chiefly reflected by the variations in the mosaic cell surface such as the presence of abnormally large cells and the deviation from their hexagonal shape. We previously reported that this device has provided good repeatability of the peripheral ECD, CV, and HEX measurements in eyes implanted with phakic intraocular lenses.…”
Section: Discussionmentioning
confidence: 99%